Reclaiming the nation : Muslim women and the law in India - Narain, Vrinda, 1965- (Toronto [Ont.] ; Buffalo [N.Y.] : University of Toronto Press, 2008)
A timely account of the struggle for liberation within a restrictive religious framework, Reclaiming the Nation is an insightful look at gender, nationhood, and the power of self-determination.
1. Introduction: Situating Indian Muslim Women -- 2. Feminism, Nationalism, and Colonialism -- 3. Post-Colonial Predicament: Muslim Women and the Law -- 4. Reclaiming the Nation.
Includes bibliographical references (pages 195-205) and index.
Print version record.
English.
JSTOR
Keywords: Muslim women -- India -- Social conditions; Muslim women -- Legal status, laws, etc. -- India; Equality before the law -- India; Sex discrimination against women -- India; Musulmanes -- Inde -- Conditions sociales; Musulmanes -- Droits -- Législation -- Inde; Égalité devant la loi -- Inde; Discrimination à l'égard des femmes -- Inde; SOCIAL SCIENCE -- Women's Studies; SOCIAL SCIENCE -- Islamic Studies; Equality before the law; Muslim women -- Legal status, laws, etc; Muslim women -- Social conditions; Sex discrimination against women; India; Muslimin; Recht; Indien